Prevalence and awareness of urinary tract infection among female secondary school students at Sekolah Menengah Kebangsaan Kubang Kerian 1 - Amin, Maanurfarhana Mohamed (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Urinary tract infection is one of infection that commonly affected female population. Substantial evidence can be found in the literature to show the prevalence as well as facts on UT1 including risk factors, sign and symptoms, treatment and complications. The general objectives of the study were to find the prevalence and awareness of UT1 among female adolescent in Sekolah Menengah Kebangsaan Kubang Kerian 1. A cross sectional study was done on 154 female students and validated questionnaires were given to students. Data was analyzed using descriptive statistic and Pearson Chi-square test. Results showed that the prevalence of UT1 among student was low which was 1.3%. As for awareness, mostly the students were highly aware regarding UT1. However, there was no association found between family relationship and awareness (p>0.05). There was also no association found between family income and student’s awareness (p>0.05). Besides that, the result also showed that there was no association between treatment seeking behavior and awareness (p>0.05). Therefore, further study need to be done to emphasized on the prevalence, preventive measures and support from family and health professionals.